A Novel Hybrid Evaluation Model for the Performance of ERP Project Based on ANP and Improved Matter-Element Extension Model. (27th March 2013) - Hui-ru, Zhao; Na-na, Li
Abstract : Considerable resources are needed when implementing the ERP project, so it is necessary to evaluate its performance. Firstly, the evaluation index system of implementation performance of the ERP project was built, and an Analytic Network Process (ANP) which can fully take the relationship between evaluation indexes into account was employed to determine the index weight. Secondly, an improved matter-element extension model, which can overcome the limitations and inadequacies of traditional matter-element extension model when performing the comprehensive evaluation, was proposed to evaluate the implementation performance of the ERP project. Finally, taking an enterprise's ERP project as an example, a comprehensive evaluation was done, and the empirical analysis result shows that this proposed hybrid evaluation model is feasible and practical.